Research methodology for adaptation policy analysis: embracing the eclectic messy centre - Purdon, Mark; Thornton, Philip K. (Edward Elgar Publishing, 2019)
This chapter tackles fundamental issues of research methodology and philosophy of science regarding adaptation policy. Importantly, the authorsdistinguish between research methods and the epistemological and ontological assumptions that underwrite research methodology. First, in terms of methods, they discuss various quantitative and qualitative policy research approaches _ often associated with exclusive epistemological positions _ which might be combined to produce new insights. Second, drawing on a meta-analysis of the adaptation policy literature, they find that the ontology of current adaptation policy and governance research is dominated by formal institutions whichleaves other salient political factors _ including ideas and interests _ in the shadows. As a path forward, theyargue that research into climate change adaptation policy be deepened to consider state_society relations and historical conditions that make effective public action possible. In practice this means expanding research ontologies beyond formal policy institutions to consider informal institutions, ideas and interests as well as actors involved.